2021
DOI: 10.1002/jez.2503
|View full text |Cite
|
Sign up to set email alerts
|

Time‐course changes in the regulation of ions and amino acids in the hard clam Meretrix lusoria upon lower salinity challenge

Abstract: In this study, we examined ion and amino acid regulation in the gill and mantle of the hard clam Meretrix lusoria. We found that the osmolality and Na + and Clconcentrations of hard clam hemolymph were significantly reduced after transferring clams from the salinity of their natural habitat [20‰ saltwater (SW)] to a lower salinity environment (10‰ SW). Specific activities of Na + , K + -ATPase (NKA), which provides the driving force for the secondary ion transport associated with cell osmoregulation in gills a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 48 publications
1
21
3
Order By: Relevance
“…However, the mantle NKA activity of those exposed to SW was significantly upregulated compared to those exposed to 20 BW, while no differences were found between those exposed to 20 BW and 10 BW (Lin et al, 2016). Although mantle NKA activity of Asian hard clams did not change upon exposure to 10 BW, we found that it was temporarily increased after the individuals were transferred to this environment (Lin et al, 2021).…”
Section: Introductioncontrasting
confidence: 64%
See 4 more Smart Citations
“…However, the mantle NKA activity of those exposed to SW was significantly upregulated compared to those exposed to 20 BW, while no differences were found between those exposed to 20 BW and 10 BW (Lin et al, 2016). Although mantle NKA activity of Asian hard clams did not change upon exposure to 10 BW, we found that it was temporarily increased after the individuals were transferred to this environment (Lin et al, 2021).…”
Section: Introductioncontrasting
confidence: 64%
“…The shortterm response of TAUT mRNA and protein expression in the gills and mantle of Asian hard clams to exposure to high-salinity SW is unknown. However, our previous study on this species revealed that gill TAUT mRNA expression was upregulated, whereas mantle TAUT mRNA expression was downregulated, and TAUT protein expression in the gills and mantle increased after the individuals were transferred from 20 to 10 BW (Lin et al, 2021). Accordingly, the transcription and/or translation of TAUT in bivalve tissues is regulated in response to salinity stress.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations